Influencia de la concentración de Ion férrico y el tiempo de agitación en el proceso de biooxidación sobre el porcentaje de recuperación de oro, de un mineral refractario. - Castillo Chávez, Andree Martin (2018)
In the present investigation the influence of ferric ion concentration and agitation time during the biooxidation process as a pretreatment was studied to increase the gold and silver recovery rate of a refractory mineral from Sayapullo by means of experimental tests in bioreactors. The sample consisted of 27 bioreactor tests, which were subjected to three different concentrations of ferric ion (8,8; 10,2 and 13) g / L and three different stirring times during the biooxidation process (24, 48 and 72) Hours , making use of two replicates for each test and then analyzing the degree of gold recovery using the fire test method or also called fire assay. The results show that, for a concentration of ferric ion of 8,8 g / L and at a time of 24, 48 and 72 hours the% gold recovery are respectively: 18,64%; 30,45% and 20,91%. For a ferric ion concentration of 10,2 g / L at a time of 24, 48 and 72 hours the% gold recovery is respectively: 30,91%; 41,82% and 19,09%. For a ferric ion concentration of 13 g / L at a time of 24, 48 and 72 hours the% gold recovery is respectively: 38,18%; 55,45% and 29,55%. It is concluded that there are increases in the recovery percentages as we raise the ferric ion concentration, but these are diminished by exceeding the 48H amount of agitation during the biooxidation process as pretreatment.